2019
DOI: 10.2478/pjmpe-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth-based nanoparticles as radiosensitizer in low and high dose rate brachytherapy

Abstract: Background: Recently bismuth-based nanoparticles have attracted increasing attention as a dose amplification agent in radiation therapy due to high atomic number, high photoelectric absorption, low cost, and low toxicity. Objectives: This study aims to calculate physical aspects of dose enhancement of bismuth-based nanoparticles in the presence of brachytherapy source by Monte Carlo simulation and an analytical method for low mono-energy. Materials and methods: After simulation and validation brachytherapy sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…102 In silico simulation tests on BiONPs of various sizes, shapes and concentrations had been performed for 125kVp, 6 MV, 10 MV and different brachytherapy sources. 9,[103][104][105][106][107] Experimentally, in vitro studies also presented different SER and DEF values by BiONPs, which were influenced by the type of radiation beam, type of cell lines used, as well as the concentrations, shapes and sizes of the BiONPs. 15,103,108 NPs may induce ROS formation in high amounts and lead to low survival fraction.…”
Section: Dovepressmentioning
confidence: 99%
“…102 In silico simulation tests on BiONPs of various sizes, shapes and concentrations had been performed for 125kVp, 6 MV, 10 MV and different brachytherapy sources. 9,[103][104][105][106][107] Experimentally, in vitro studies also presented different SER and DEF values by BiONPs, which were influenced by the type of radiation beam, type of cell lines used, as well as the concentrations, shapes and sizes of the BiONPs. 15,103,108 NPs may induce ROS formation in high amounts and lead to low survival fraction.…”
Section: Dovepressmentioning
confidence: 99%
“…These changes can weaken the photothermal effect and radiosensitization (Figures S8 and S9). Nevertheless, in the case of PVP-Bi/GO, the morphology and crystalline structures of BiNPs are still maintained for doses up to 12 Gy (Figure c). Even at a dose of 18 Gy, there is only a slight change in their size, however no significant decrease in performance (Figure S10).…”
Section: Resultsmentioning
confidence: 97%
“…8, 14 Investigations on bismuth NPs complexes as radiosensitizers have been conducted with external and internal radiotherapy, which enhance radiation effects. [15][16][17] Our previous works also had concluded that bismuth oxide (Bi 2 O 3 ) NPs (BiONPs) with photon beams could generate ROS that influence radiosensitization effects. Prior research using 150 MeV proton, 6 MV photon and 6 MeV electron beams had found that the higher sensitization enhancement ratios (SER) in cancer cells would induce a higher amount of ROS.…”
Section: Introductionmentioning
confidence: 99%